PARADIGM SHIFT: HOW THE DIGITAL ECONOMY IS REORGANISING THE WORLD'S ECONOMIC POWER - Pemy Christiaan; Nofirman Nofirman (CV. Adiba Aisha Amira, 2024)
The digital economy has led to a fundamental paradigm shift in the power structure of the global economy. Digital technologies, such as artificial intelligence, big data, and the Internet of Things (IoT), play an important role in improving countries' productivity, innovation, and competitiveness. Countries that are able to adopt and implement these technologies effectively tend to experience faster economic growth. In addition, the digital economy is also expanding economic inclusion by enabling greater access to markets and financial services for individuals and small businesses, especially in developing countries. However, this transformation also brings challenges, including digital inequality and the need for adequate regulation. Policies that support education, digital infrastructure and data protection, as well as increased international cooperation, are essential to maximise the benefits of the digital economy in an equitable and sustainable manner.